Bidding and Performance in Repo Auctions: Evidence from ECB Open Market Operations - Kjell G. Nyborg; Ulrich Bindseil; Ilya A. Strebulaev (Fondazione Eni Enrico Mattei (FEEM), 2005)
Repo auctions are used to inject central bank funds against collateral into the banking sector. The ECB uses standard discriminatory auctions and hundreds of banks participate. The amount auctioned over the monthly reserve maintenance period is in principle exactly what banks collectively need to fulfil reserve requirements. We study bidder-level data and find: (i) Bidder behavior is different from what is documented for treasury auctions. Private information and the winners curse seem to be relatively unimportant. (ii) Underpricing is positively related to the difference between the interbank rate and the auction minimum bid rate, with the latter appearing to be a binding constraint. (iii) Bidders are more aggressive when the imbalance of awards in the previous auction is larger. (iv) Large bidders do better than small bidders. Some of our findings suggests that bidders are concerned with the losers nightmare and have limited amounts of the cheapest eligible collateral.
Keywords: G21; G12; D44; E43; E50; 330; Repo auctions; Multiunit auctions; Reserve requirements; Losers nightmare; Money markets; Central bank; Collateral; Open market operations; Zentralbank; Pensionsgeschäft; Offenmarktpolitik; Geldmarkt; Europäische Wirtschafts- und Währungsunion; EU-Staaten